Improving spot‐scanning proton therapy patient specific quality assurance with HPlusQA, a second‐check dose calculation engine. Issue 12 (12th November 2013) - Mackin, Dennis; Li, Yupeng; Taylor, Michael B.; Kerr, Matthew; Holmes, Charles; Sahoo, Narayan; Poenisch, Falk; Li, Heng; Lii, Jim; Amos, Richard; Wu, Richard; Suzuki, Kazumichi; et al.
Abstract : Purpose: : The purpose of this study was to validate the use of HPlusQA, spot‐scanning proton therapy (SSPT) dose calculation software developed at The University of Texas MD Anderson Cancer Center, as second‐check dose calculation software for patient‐specific quality assurance (PSQA). The authors also showed how HPlusQA can be used within the current PSQA framework. Methods: : The authors compared the dose calculations of HPlusQA and the Eclipse treatment planning system with 106 planar dose measurements made as part of PSQA. To determine the relative performance and the degree of correlation between HPlusQA and Eclipse, the authors compared calculated with measured point doses. Then, to determine how well HPlusQA can predict when the comparisons between Eclipse calculations and the measured dose will exceed tolerance levels, the authors compared gamma index scores for HPlusQA versus Eclipse with those of measured doses versus Eclipse. The authors introduce the αβγ transformation as a way to more easily compare gamma scores. Results: : The authors compared measured and calculated dose planes using the relative depth, z/R × 100%, where z is the depth of the measurement and R is the proton beam range. For relative depths than less than 80%, both Eclipse and HPlusQA calculations were within 2 cGy of dose measurements on average. When the relative depth was greater than 80%, the agreement between the calculations and measurements fell to 4 cGy. For relative depths less than 10%, the Eclipse and HPlusQA dose discrepancies showed a negative correlation, −0.21. Otherwise, the correlation between the dose discrepancies was positive and as large as 0.6. For the dose planes in this study, HPlusQA correctly predicted when Eclipse had and had not calculated the dose to within tolerance 92% and 79% of the time, respectively. In 4 of 106 cases, HPlusQA failed to predict when the comparison between measurement and Eclipseˈs calculation had exceeded the tolerance levels of 3% for dose and 3 mm for distance‐to‐agreement. Conclusions: : The authors found HPlusQA to be reasonably effective (79% ± 10%) in determining when the comparison between measured dose planes and the dose planes calculated by the Eclipse treatment planning system had exceeded the acceptable tolerance levels. When used as described in this study, HPlusQA can reduce the need for patient specific quality assurance measurements by 64%. The authors believe that the use of HPlusQA as a dose calculation second check can increase the efficiency and effectiveness of the QA process.